PENINGKATAN KEKUATAN SERAT SERABUT KELAPA DENGAN PERLAKUAN SILANE - Seno Darmanto (Universitas Muhammadiyah Semarang, 2011)
Research is done to analyze treatment (physical and chemical) inincreasing quality of coir fiber. Sequential of coir fiber research is done withdetermining characteristic of physically coir fiber, methd of making single fiber, treatment technical and testing of strength. Determining of physically coir fiber characteristic is done by observing and measuring dimension directly and tesling water content. Then making of single fiber is done by selecting of coir fiber, washing, dryrng and brushing/shaving, Treatment of physically coir fiber is begun from coir fiber in outer shell of coconut to single fiber. Kind of physically treatment consists of washing, soaking, natural drytng and supervised drying. Iilashing and soahng use water. Nalural drying of ccir fiber is done wheit coir fiber is outer shell of coconut. Supervised drying is done with hot air in +45'C of tempemture. The next, washing, soaking and supervised drying is done to preryrecoir fiber that will be used to chemical treatment. Chemical treqtment is done with silane method. Silane treatment for single coirfiber is done with using silane agent solution. The silane solution is arranged with concentration variation 1%, 2%, 3%, 494up to l0%. Silane treatment uses methanol as solvent. Testing of single coir fiber is done accordingwith refer JIS number R7601 for single fiber. And testing of tensile shows that silane treatrnent will trend to increase strength. The increasing of coir strength andwill be optimum in concentration 7%o of silane agent.Key word: coirfiber, silane treatment, strength